Toward a Greater Kerguelen large igneous province: Evolving mantle source contributions in and around the Indian Ocean - Olierook, H.; Merle, R.; Jourdan, Fred (Elsevier BV, 2017)
© 2017 Elsevier B.V.The link between the Kerguelen large igneous province and several moderately-voluminous magmatic domains emplaced on continental crust near the relict triple junction of eastern Gondwana remains tentative. In particular, linking Sr–Nd–Pb isotopic ratios of the 90,000 km2 submerged Naturaliste Plateau at the relict triple junction of eastern Gondwana to the Kerguelen LIP were difficult due to previous age estimates of ca. 100 Ma. Sericite hydrothermal plateau ages as old as 127.6 ± 0.6 Ma indicate that the volcanism on the plateau began at or prior to ca. 128 Ma, which is > 25 m.y. older than previous estimations. These ages are closely matched by the then-nearby ca. 140–130 Ma Comei, 137–130 Ma Bunbury, 124 Ma Wallaby Plateau and 118–117 Ma Rajmahal-Bengal-Sylhet magmatic provinces. The Sr–Nd–Pb isotopic characteristics of the majority of these ca. 140–117 Ma circum-eastern Gondwana magmatic provinces display only source contributions from the depleted asthenosphere and lithosphere with negligible contribution from the Kerguelen mantle plume. The Comei Province shows a direct plume-related melt signature, probably because it sits directly in the center of the modeled plume head position at 140–130 Ma. We suggest that the Kerguelen mantle plume provided the additional heat necessary to melt the asthenosphere and lithosphere of the circum-eastern Gondwanan magmatic provinces. Only after the motion of the Kerguelen plume head into the nascent Indian Ocean at ca. 100–95 Ma does a significant melt contribution from the Kerguelen mantle plume become evident in the isotopic signature, a signal that persists until the present-day. Despite differences in source contributions over time, it is clear that the Kerguelen mantle plume is necessary for the production of all the circum-eastern Gondwana magmatic domains, which we propose should be referred to as the Greater Kerguelen Large Igneous Province.